Thermodynamic Study of 4-n-Alkyloxybenzoic Acids - Fonseca, JMS (2010)
The Knudsen mass-loss effusion technique was used for measuring the vapor pressures at different temperatures of the following 4-n-alkyloxybenzoic acids: 4-methoxybenzoic acid, between (340 and 362) K; 4-ethoxybenzoic acid, between (349 and 373) K; 4-propoxybenzoic acid, between (345 and 365) K; 4-butoxybenzoic acid, between (351 and 373) K; 4-pentyloxybenzoic acid, between (355 and 377) K; 4-hexyloxybenzoic acid, between (363 and 379) K; 4-heptyloxybenzoic acid, between (355 and 361) K; and 4-octyloxybenzoic acid, between (363 and 372) K. From the temperature dependence of the vapor pressure of each crystalline compound, the standard (p(0) = 10(5) Pa) molar enthalpies and Gibbs energies of sublimation, at T = 298.15 K, were derived. Differential scanning calorimetry was used in the study of phase transitions between condensed phases. The measured thermodynamic properties are compared with the results obtained on a previous similar study concerning the 4-n-alkylbenzoic acids series.